Influence of PCBM Nanocrystals on the Donor-Acceptor Polymer Ultraviolet Phototransistors - Hong Zhu; Quanhua Chen; Lijian Chen; Rozalina Zakaria; Min-Su Park; Chee Leong Tan; Li Zhu; Yong Xu (Nanomaterials)
Organic phototransistors, renowned for their exceptional biocompatibility, hold promise in phototherapy for tracking the efficacy of photosensitive drugs within treatment areas. Nevertheless, it has been found that organic semiconductors are less effective in detecting ultraviolet (UV) light because of their narrow bandgap. Here, we show that UV photodetection in phototransistors using donor-acceptor (D-A) polymer semiconductors can be significantly enhanced by incorporating PCBM nanocrystals. This integration results in a band mismatch between the nanocrystals and the D-A polymer at the interface. These nanocrystals also demonstrate a notable capability of modulating threshold voltage under UV light. The devices incorporating nanocrystals exhibit a photoresponsivity of 0.16 A/W, surpassing the photoresponsivity of the devices without nanocrystals by 50%. The specific detection rate of devices with nanocrystals is around 2.00 × 1010 Jones, which is twice as high as that of devices without nanocrystals. The presented findings offer a potential avenue to improve the efficiency of polymer phototransistors for UV detection.